Modeling of Long Lasting Functional State of Healthiness Dynamics - Berškienė, K.; Navickas, Z.; Vainoras, A. (Elektronika ir Elektrotechnika, 2006)
The statistics claims, that people who are not physically active live shorter and they are ill more often. However, only individual physical activity is useful. Human organism adaptation to physical load peculiarities and opportunities is an actual task of physiology, sports and clinical medicine. For the solution of this task we analyzed the integral health evaluation and formalized effect models. We suggested to formalize and mathematically describe these models by the convolution of Mealy and Moore automata. This model could be applied for the automation of making diagnosis or help to organize the feedback between patient functional state and applied influence. lll. 4, bibl. 7 (in English; summaries in English, Russian and Lithuanian).